Assessing the disease burden of Yi people by years of life lost in Shilin county of Yunnan province, China - Lv Yi-Ling; Wan Chong-Hua; Cai Le; Zhou Shang-Cheng; Fang Peng-Qian (BMC, 2009)
Abstract Background Years of Life Lost (YLL) is one of the methods used to estimate the duration of time lost due to premature death. While previous studies of disease burden have been reported using YLL, there have been no studies investigating YLL of Yi people in rural China. Yunnan Province ranks first in terms of Yi people in China. This paper uses YLL to estimate the disease burden of Yi people in Shilin county of Yunnan Province. This study aims to address the differentials about YLL between Yi people and Han people for providing useful information for health planning. Methods We applied the Global Burden of Disease (GBD) method created by WHO. YLL rate per 1,000 were calculated from medical death certificates in 2003 in Shilin Yi Nationality Autonomous County (Shilin county). Results The male had greater YLL rate per 1,000 than did the female almost in each age group. It demonstrated a higher premature mortality burden due to injuries in Shilin county. Among the top non-communicable diseases, respiratory diseases are the most common mortality burden. Yi people are still suffering from maternal conditions, with two times the burden rates of Han people. For Yi people, while malignant neoplasm was one of the least burden of disease for male, it was the greatest for female, which is the opposite to Han people. Conclusion Strategies of economic development should be reviewed to enhance the prevention and treatment of injuries, maternal conditions and respiratory diseases for Yi people.